2000
DOI: 10.1006/viro.2000.0604
|View full text |Cite
|
Sign up to set email alerts
|

The Human T-Cell Leukemia Virus Type I (HTLV-I) X Region Encoded Protein p13II Interacts with Cellular Proteins

Abstract: Interactions between the Human T-cell leukemia virus type I (HTLV-I) gene product p13(II) and cellular proteins were investigated using the yeast two-hybrid system. Variant forms of p13(II) were derived from two HTLV-I molecular clones, K30p and K34p, that differ in both virus production and in vivo and in vitro infectivity. Two nucleotide differences between the p13 from K30p (p13K30) and K34p (p13K34) result in a Trp-Arg substitution at amino acid 17 and the truncation of the 25 carboxyl-terminal residues of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Whether this form represents a bona fide p13 II -p13 II dimer, a complex with other proteins, or rather, results from natural post-translational modifications of p13 II or chemical modifications arising during mitochondrial isolation is under investigation. In this connection it is worth mentioning that interactions between p13 II and cellular proteins have been described in a yeast 2-hybrid screen (33). This analysis identified two binding partners for p13 II coded by the K34 molecular clone, C44, a protein that shows substantial similarities to archaeal adenylate kinases, and C254, a protein that probably corresponds to non-muscle filamin.…”
Section: Htlv-1 P13 II Function 34431mentioning
confidence: 86%
“…Whether this form represents a bona fide p13 II -p13 II dimer, a complex with other proteins, or rather, results from natural post-translational modifications of p13 II or chemical modifications arising during mitochondrial isolation is under investigation. In this connection it is worth mentioning that interactions between p13 II and cellular proteins have been described in a yeast 2-hybrid screen (33). This analysis identified two binding partners for p13 II coded by the K34 molecular clone, C44, a protein that shows substantial similarities to archaeal adenylate kinases, and C254, a protein that probably corresponds to non-muscle filamin.…”
Section: Htlv-1 P13 II Function 34431mentioning
confidence: 86%
“…During viral infection, p12 I may function by facilitating escape from immune surveillance activity, leading to unchallenged clonal expansion of infected T cells in the PB and CNS, and a subsequent overall increase in proviral DNA load. p13 II , an 87 amino acid protein, has been shown to primarily localize to the mitochondria and interact with several cellular proteins (Hou et al, 2000) (Fig. 2).…”
Section: Viral Mechanisms Regulating Htlv-i Infection In Target Cellsmentioning
confidence: 99%
“…Thus far, it has not been demonstrated that p13 nylate kinases, the eukaryotic homologues of which localize to mitochondria. Interestingly, the human homologue of C44 is expressed in the Jurkat T-cell line and proliferating, but not resting, PBMC (57). The implications of this finding remain unclear but allow speculation about a potential role of p13 II in cellular activation.…”
Section: Mitochondria: Target Of Px Orf II P13 Iimentioning
confidence: 99%